2008
DOI: 10.1186/1478-811x-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction: RNA interference-mediated gene silencing in murine T cells: in vitro and in vivo validation of proinflammatory target genes

Abstract: Background: T cells play a central role in many inflammatory diseases, hence the identification and validation of T cell-specific target genes will increase the understanding of T cell function in pathologic inflammatory situations. RNA interference (RNAi), with its ability to induce specific gene silencing in mammalian cells, represents a powerful technology to investigate and validate the function of pharmaceutical target genes in vitro and in vivo. The aim of the present study was to systematically explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…As a third approach to investigate the role of Itk in T‐cell function, RNA interference (RNAi) experiments were performed (38–40). To test whether Itk knockdown in human T cells leads to impaired T‐cell activation comparable to the situation observed in Itk knockout mice and in mice treated with the Itk inhibitor, purified human T cells were transfected with Itk‐specific or control siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…As a third approach to investigate the role of Itk in T‐cell function, RNA interference (RNAi) experiments were performed (38–40). To test whether Itk knockdown in human T cells leads to impaired T‐cell activation comparable to the situation observed in Itk knockout mice and in mice treated with the Itk inhibitor, purified human T cells were transfected with Itk‐specific or control siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Gene silencing appears to be more efficient if T-cells are activated through the TCR either alone or in combination with CD28 before electroporation/nucleofection [37,42,49,50], which correlates with studies that have reported higher levels of gene expression in activated primary T-cells using plasmids compared with nonactivated T-cells [28,30,32]. Gene silencing appears to be more efficient if T-cells are activated through the TCR either alone or in combination with CD28 before electroporation/nucleofection [37,42,49,50], which correlates with studies that have reported higher levels of gene expression in activated primary T-cells using plasmids compared with nonactivated T-cells [28,30,32].…”
Section: Mechanismmentioning
confidence: 99%
“…For example, knockdown of the tyrosine kinase ZAP-70 in murine T-cells via nucleofection with siRNAs, followed by adoptive transfer of these cells into recipient mice suppresses delayed type hypersensitivity (a Th1-mediated inflammatory response) [49]. For example, knockdown of the tyrosine kinase ZAP-70 in murine T-cells via nucleofection with siRNAs, followed by adoptive transfer of these cells into recipient mice suppresses delayed type hypersensitivity (a Th1-mediated inflammatory response) [49].…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, flow cytometric analysis should be run using the pancreata of 25-30 week-old wild type mice to confirm the expression of the desired proteins on a cell's surface [28,29], as RNA quantities obtained from microarray data do not always correlate with protein expression and occasionally yield false positives. Celltype-specific gene knock-out experiments can also be performed, either through in-vivo mouse models or in-vitro methods including standard siRNA procedures [30,31]. The use of these procedures can directly confirm the significance of the chosen genes in pancreatic Treg function and survival [32,33].…”
Section: Future Investigationsmentioning
confidence: 99%